Sputtering of silicon nanopowders by an argon cluster ion beam - Zeng, Xiaomei; Pelenovich, Vasiliy; Wang, Zhenguo; Zuo, Wenbin; Belykh, Sergey; Tolstogouzov, Alexander; Fu, Dejun; Xiao, Xiangheng (Beilstein Journal of Nanotechnology, 2019)
In this work an Ar+ cluster ion beam with energy in the range of 10–70 keV and dose of 7.2 × 1014–2.3 × 1016 cluster/cm2 was used to irradiate pressed Si nanopowder targets consisting of particles with a mean diameter of 60 nm. The influence of the target density and the cluster ion beam parameters (energy and dose) on the sputtering depth and sputtering yield was studied. The sputtering yield was found to decrease with increasing dose and target density. The energy dependence demonstrated an unusual non-monotonic behavior. At 17.3 keV a maximum of the sputtering yield was observed, which was more than forty times higher than that of the bulk Si. The surface roughness at low energy demonstrates a similar energy dependence with a maximum near 17 keV. The dose and energy dependence of the sputtering yield was explained by the competition of the finite size effect and the effect of debris formation.
Keywords: finite size effect; gas cluster ion beam; silicon nanoparticles; smoothing effect; sputtering

(untitled) - Matsuo, J.; Toyoda, N.; Yamada, I. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 1996)

Sputtering by Particle Bombardment I - Sigmund, P. (Sputtering by ion bombardment theoretical concepts, 1981)

(untitled) - Insepov, Z.; Yamada, I. (Nucl. Instrum. Methods Phys. Res., Sect. B, 1996)

(untitled) - Birtcher, R. C.; Matsuo, J.; Yamada, I. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2001)

(untitled) - Toyoda, N.; Matsuo, J.; Yamada, I. (AIP Conf. Proc., 1997)

(untitled) - Insepov, Z.; Yamada, I. (Nucl. Instrum. Methods Phys. Res., Sect. B, 1999)

(untitled) - Toyoda, N.; Hagiwara, N.; Matsuo, J.; Yamada, I. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2000)

(untitled) - Matsuo, J.; Toyoda, N.; Akizuki, M.; Yamada, I. (Nucl. Instrum. Methods Phys. Res., Sect. B, 1997)

(untitled) - Ieshkin, A. E.; Ermakov, Y. A.; Chernysh, V. S. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2015)

(untitled) - Chernysh, V. S.; Ieshkin, A. E.; Ermakov, Y. A. (Appl. Surf. Sci., 2015)

(untitled) - Mashita, T.; Toyoda, N.; Yamada, I. (Jpn. J. Appl. Phys., 2010)

(untitled) - Sumie, K.; Toyoda, N.; Yamada, I. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2013)

(untitled) - Isogai, H.; Toyoda, E.; Senda, T.; Izunome, K.; Kashima, K.; Toyoda, N.; Yamada, I. (AIP Conf. Proc., 2006)

(untitled) - Seki, T.; Murase, T.; Matsuo, J. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2006)

(untitled) - Ichiki, K.; Ninomiya, S.; Seki, T.; Aoki, T.; Matsuo, J. (AIP Conf. Proc., 2011)

(untitled) - Kissel, R.; Urbassek, H. M. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2001)

(untitled) - Järvi, T. T.; Pakarinen, J. A.; Kuronen, A.; Nordlund, K. (EPL, 2008)

(untitled) - Järvi, T. T.; Nordlund, K. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2012)

(untitled) - Zimmermann, S.; Urbassek, H. M. (Int. J. Mass Spectrom., 2008)

(untitled) - Nietiadi, M. L.; Sandoval, L.; Urbassek, H. M.; Möller, W. (Phys. Rev. B, 2014)

(untitled) - Urbassek, H. M.; Nietiadi, M. L.; Bradley, R. M.; Hobler, G. (Phys. Rev. B, 2018)

(untitled) - Sandoval, L.; Urbassek, H. M. (Nanoscale Res. Lett., 2015)

(untitled) - Klimmer, A.; Ziemann, P.; Biskupek, J.; Kaiser, U.; Flesch, M. (Phys. Rev. B, 2009)

(untitled) - Greaves, G.; Hinks, J. A.; Busby, P.; Mellors, N. J.; Ilinov, A.; Kuronen, A.; Nordlund, K.; Donnelly, S. E. (Phys. Rev. Lett., 2013)

(untitled) - Ilinov, A.; Kuronen, A.; Nordlund, K.; Greaves, G.; Hinks, J. A.; Busby, P.; Mellors, N. J.; Donnelly, S. E. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2014)

(untitled) - Yang, L.; Seah, M. P.; Anstis, E. H.; Gilmore, I. S.; Lee, J. L. S. (J. Phys. Chem. C, 2012)

(untitled) - Belykh, S. F.; Tolstogouzov, A. B.; Lozovan, A. A. (J. Surf. Invest.: X-Ray, Synchrotron Neutron Tech., 2015)

(untitled) - Pelenovich, V. O.; Zeng, X. M.; Ieshkin, A. E.; Chernysh, V. S.; Tolstogouzov, A. B.; Yang, B.; Fu, D. J. (J. Surf. Invest.: X-Ray, Synchrotron Neutron Tech., 2019)

(untitled) - Karnbach, R.; Joppien, M.; Stapelfeldt, J.; Wörmer, J.; Möller, T. (Rev. Sci. Instrum., 1993)

(untitled) - Gspann, J.; Körting, K. (J. Chem. Phys., 1973)

(untitled) - Yamada, I.; Matsuo, J.; Insepov, Z.; Takeuchi, D.; Akizuki, M.; Toyoda, N. (J. Vac. Sci. Technol., A, 1996)

(untitled) - Baranov, I.; Della-Negra, S.; Domaratsky, V.; Chemezov, A.; Novikov, A.; Obnorsky, V.; Pautrat, M.; Anders, C.; Urbassek, H. M.; Wien, K.; Yarmiychuk, S.; Zhurkin, E. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2008)

(untitled) - Seki, T.; Matsuo, J. (AIP Conf. Proc., 2006)

(untitled) - Seah, M. P. (J. Phys. Chem. C, 2013)